The Mediating and Buffering Effect of Creativity on the Relationship Between Sense of Place and Academic Achievement in Geography - Zhang, Jianzhen; Ge, Jiahao; Ma, Yuting; Wang, Ziyang; Yu, Yuyao; Liang, Xiaoyu; An, Zhenni; Xu, Yanhua (Frontiers in Psychology, 2022)
Purpose: This study explored the relationship between sense of place and academic achievement in geography and used a mediation model to verify the mediating role of creativity in this relationship. Methods: A total of 1,037 upper-secondary-school students were surveyed using the Sense of Place Scale, the Innovative Behavior Scale, and their geography test scores. SPSS (version 26.0) was used for descriptive statistical analysis and correlation analysis. The PROCESS plug-in (version 4.0) was used to test the mediating effect of creativity. Results: (1) The correlation analysis showed that sense of place has a positive effect on academic achievement in geography and is related to creativity. Moreover, creativity exerts a positive effect on academic achievement in geography. (2) The results of mediation analysis indicated that creativity plays mediating and buffering roles in the relationship between sense of place and academic achievement in geography after controlling for gender and residential address. The direct and indirect effects accounted for 65.708% and 34.292% of the total effect, respectively. Conclusions: The results indicated that sense of place not only affected academic achievement in geography directly but also indirectly through creativity. This conclusion provides certain ideas for the development of geography curriculums. Since academic achievement in geography is related to both sense of place and creativity, it is necessary to pay more attention to integrating sense of place in geography education and to foster creativity in curriculum development and teaching of geography.